Developing LMS for Project-Based Learning to Enhance Web Programming Skills in Students - Titah Pertiwi, Widya; Sujatmiko, Bambang (Journal of Education Technology and Information System, 2025)
Abstract. The Learning Management System (LMS) named "BrainBoost" was designed by researchers to determine the differences and increase students' cognitive and psychomotor competencies in web server side scripting programming based on Project Based Learning (PJBL). This research adopts an R&D (Research and Development) approach. The ADDIE model became the basis for designing and carrying out this research. The creation of this website developed LMS MOODLE version 4.4 using vscode software with the programming language PHP (Hypertext Preprocessor) version 8.1.25 and JS (Java Script). The database uses MySQL and the online compiler used is CodeMirror version 5. Analysis of learning media, teaching materials, test questions, and Learning Implementation Plans (RPP) shows a high level of conformity with validity criteria. The percentage of validation assessments for each device reached a very satisfactory figure, with media at 91.2%, material at 96%, test questions at 95.45%, and lesson plans at 86.66%. Based on expert assessments, this learning media has a very high level of validity, namely 92.32%. These results indicate that the media has met the criteria and is ready to be used in the learning process. The average cognitive pretest score is 48.60. The average score for the cognitive posttest was 88. The results of the analysis showed that the average score for students' psychomotor abilities increased significantly from 55 in the pretest to 88.6 in the posttest. Hypothesis results in cognitive tests and psychomotor tests using the paired T-test show a Sig. (2 tailed) <.001. This study shows that implementing an LMS can effectively increase student competency in the Web Programming subject class XII RPL 1 at SMKN 2 Surabaya. Keywords: ADDIE; Cognitive; Learning Management System (LMS); Project-Based Learning; Psychomotor